PENDAMPINGAN PROGRAM PENINGKATAN KETERAMPILAN TEKNIK PEMBENTUKAN LOGAM DI KELOMPOK USAHA KECIL DI KABUPATEN BEKASI - Sukarman, Sukarman; Karyadi, Karyadi; Khoirudin, Khoirudin; Mulyadi, Dodi; Fazin, Nazar; Irfani, Tomas; Miftahudin, Moh (Jurnal Pengabdian Masyarakat Polmanbabel, 2024)
The material manufacturing process involving the deep drawing process is often challenging in small and medium industries. That is due to the many complicated parameters that must be overcome during the process. The deep drawing is a complex steel forming process because it involves blank dimensions, dimension/height ratio (D/H ratio), and die/punches tolerance (D/P allowance). Failure to identify blank dimensions and D/H ratio will result in defects in the production process, such as tears and wrinkles. This service aims to help MSMEs overcome common failures in production processes involving deep drawing. This community service article discusses technology dissemination to small business groups (UKM) for the deep drawing process in producing R-ornament #3D40x40 components involving these three variables. R-ornament #3D40x40 is produced using SPCC-SD material with a thickness of 0.8 mm. The participatory action research (PAR) method approach assists MSMEs in optimizing blank dimensions, D/H ratio, and D/P allowance simultaneously with partners. Identification of a D/P allowance of 1.41 mm has eliminated wrinkle defects in the product. Identifying deep drawing parameters has helped MSMEs overcome the production process so that tearing and wrinkle defects do not occur.